THE EFFECT OF MILITANCY ON DEVELOPMENT AND ECONOMY OF A COMMUNITY: A STUDY OF ACTIVITIES OF MILITANTS IN NIGER DELTA - Obasi francis eze, (IJRDO - Journal of Business Management, 2020)
Community Development issue has taken centre stage in the development needs of rural communication in the Niger delta. The federal government and multinational oil companies operating in the zone failed to fulfill its obligation of development to the people of Niger delta. However, it was observed that the issue of community development was relegated to the background as the people focus was shifted from that of the good of the community to themselves, waiting for government to provide the needed social and economic infrastructure. The study focuses on the effect of militancy on development and economy of a community in Niger delta. To better under study this I, anchor the theoretical framework on development on development theory of Dudley seers. The theory state that development is that situation of the living standard of individuals within a given society has improved. The theory is relevant to this study because it underscores the underlining causes of violence in the region, the research methodology adopted exploratory and explanatory approach while questionnaire and personnel observation were used in retrieving required data from the public. 92 respondents were selected randomly from the groups namely: Traditional rulers, council of elders, youth’s movement and women leaders. Single percentages were used to analyze the data and also chi-square method was used in solving the hypothesis. The reliability coefficient for the effect of militancy on development and economy of community participation Questionnaire (EMECDAQ) was found to be positive. Four research questions and four hypotheses were raised in the study. The findings reveal that politics of oil, underdevelopment, environment degradation, Gas flaring and Economic are the root causes of militancy operations in the Niger delta. The study recommends that the south-south zone should be adequately funded and its projects should be increased alongside other developmental responsibility. The multinational co-operation and government should come up with special plan for the zone to enable them have a good relationship.